Preventing mental health symptoms in adolescents using dialectical behaviour therapy skills group: a feasibility study. Issue 1 (2nd January 2018) - Burckhardt, Rowan; Manicavasagar, Vijaya; Shaw, Frances; Fogarty, Andrea; Batterham, Philip J.; Dobinson, Katie; Karpin, Ilana
Abstract: Previous prevention programmes have largely focused on the emotion regulation strategy of cognitive reappraisal. The present study is a feasibility trial that evaluates a prevention programme that teaches cognitive reappraisal, acceptance and problem-solving strategies. Ninety-six Year 10 high school students were randomly allocated to either the intervention or control condition. All participants completed scales evaluating emotion regulation difficulties, depression, anxiety and anger at baseline, post-intervention and at 6-month follow-up. In addition, the intervention condition completed a workshop evaluation questionnaire at post-intervention that included qualitative items. Mixed models for repeated measures and content analysis were used to analyse the data. Results suggested there were no statistical differences between the conditions although effect sizes suggested a small advantage favouring the control condition. On the qualitative evaluation, however, most participants reported important benefits in relation to improved emotion regulation abilities. These contrasting results are discussed and suggestions made for future research.